Should Engineering Ethics be Taught? - Abaté, Charles (Science & Engineering Ethics, 2011)
Should engineering ethics be taught? Despite the obvious truism that we all want our students to be moral engineers who practice virtuous professional behavior, I argue, in this article that the question itself obscures several ambiguities that prompt preliminary resolution. Upon clarification of these ambiguities, and an attempt to delineate key issues that make the question a philosophically interesting one, I conclude that engineering ethics not only should not, but cannot, be taught if we understand 'teaching engineering ethics' to mean training engineers to be moral individuals (as some advocates seem to have proposed). However, I also conclude that there is a justification to teaching engineering ethics, insofar as we are able to clearly identify the most desirable and efficacious pedagogical approach to the subject area, which I propose to be a case study-based format that utilizes the principle of human cognitive pattern recognition.